Financing the transformation of food systems under a changing climate: key messages - Millan, Alberto (2019)
The global food system will need to produce food more efficiently and sustainably to achieve the Sustainable Development Goals (SDGs) and meet the 2°C climate commitments of the Paris Agreement. As climate change affects food systems, governments, food and agriculture companies, and public and private investors need to better identify and address the numerous climate- related risks they face. This can also be an inflection point to take advantage of new investment opportunities that the transformation to low-carbon and resilient food systems presents. Climate-smart investments to transform food systems, however, are not yet at scale. This will require addressing core market failures to unlocking private sector financing from food and agriculture companies, domestic and international financial institutions, and specialized investors. Whilst this paper highlights the clear need and role for the former, it explores in greater depth innovative strategies to address the core market failures of the latter: 1) lack of deep pipeline of bankable projects, today; 2) high investment risk and lack of primary data/information asymmetries; and 3) lack of intermediation to efficiently connect different pools of capital to investment.